Graphene Based 1-D Photonic Crystal Waveguide for Delay Tuning - Garg, Ashina (My University, 2016)
A 1-dimensional (1-D) photonic crystal waveguide based on graphene which is electrically controllable is investigated to achieve slow light having wide bandwidth, low value of group velocity vg and high value of group index ng. The photonic crystal (PC) devices have an edge over other materials since they can work on room temperature, on chip integration is highly suitable, and have low dispersion propagation and wider bandwidth. Photonic crystal waveguides (PCW) find applications for tuning the delay as they provide tunable slow light with wide bandwidth Our proposed structure has a 1-D PCW which is created through a photonic crystal which is otherwise perfect by introduction of a line defect. The bandgap of the PC locates some defect states within it by removal of a central slab of air to obtain an appropriate waveguide design. The light having propagation inside the waveguide has the constraint that it must move with a frequency which is within the crystal’s bandgap and it can be made to move along the waveguide. A layer of graphene is inserted in the 1-D PCW to improve the properties of structure further and thus tune the delay by varying the graphene’s fermi energy level. Graphene’s excellent electrical tuning properties have various advantages and they are taken into consideration for tuning the group delay in a PCW. When graphene is not used in the structure, a value of 54.46ps for group delay is noted which is large enough and that too with a very large applied voltage of 50V, which is not practically realizable for applications involving tuning of delay on chip. Whereas when graphene is used in the design i.e. with core and clad; as the voltage applied to graphene is altered from 1 volt to 4 volts, there is a tuning from 81.1ps to 204.49ps in the group delay value for the structure where core region has graphene on it; and from 50.45ps to 187.6ps where clad region has graphene applied at 1550nm wavelength. Thus, a group delay tuning of 123.39 picoseconds and 137.15 picoseconds is achieved in both the designs respectively which is large enough as compared to 2-D PCW structures. The slow light which is then achieved has many useful applications in signal processing and delay scanning in the optical domain.
Masters of Engineering-ECE
Keywords: Photonic Crystal waveguide; Slow Light; Graphene; Delay Tuning; Electronics and Communication